Pemberdayaan Masyarakat dalam Pembuatan Sabun Padat dari Daun Sirih (Piper betle L.) - Hendra K. Maury; Indah W. Tambunan; Alin S.D. Yampy; Wulan N. Anwari; Chesiana Chesiana; Marlifon Merani; Vanessa Y.A. Brabar; Sara D. Lemauk; Urinsi Pattaru; Dames Kogoya; Oktafianti A. Nurafifah; Yuliance A. Nawipa; Jovita L. Kayame (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
Covid-19 is an infection channel in human respiratory caused by coronavirus, which spread all over the world in 2020, thus implementing lockdown to lower the spread of the corona virus. Because Covid-19 communities have a reduced income especially in birds watching Isyo Hills in Nimbokrang especially in Muaif Village, and in Rhepang village it has a rich diversity of life, including betle leaves, where betle leaves have many benefits and properties such as betlephenol, saponin, sesterypen, starch, kovikol, where a natural antiseptic agent is available, The purpose of this activities is to make a solid soap of betel leaves (Piper betle L.) as antibacterias, and to support the economic growth of people in reple-betel leavesÂ  is 10%, and the cost of rhi-leaf extract is 15 g, the respondents of society are 82% approved, 18% agree once in "a compact soap tutorial of the betel leaf," and 73%, 45%, and 64% in turn favor to smell, shape, and the color of the soap. Then, according to 73% of participants feel the tools and materials used in the manufacture of soap. And finally, the number of attendees who filled the questionnaire's list was attracted to making solid soap after a solid soapmaking tutorial.Keyword: antibacteria; betel leaves; Covid-19; Rhepang Muaif villages; solid soap